Revisiting Mercy in Jude: Intervention, Intercession, and the Intruders - Prothro, James B. (Journal for the study of the New Testament, 2025)
Though it is often read merely as a letter of condemnation, theological and literary studies have opened up new vistas for understanding Jude’s argument, theological outlook, and its positive call for the addressees to have ‘mercy’ and save those in danger of eschatological ‘fire’. Debate remains, however, as to the scope of such commands and whether Jude’s soteriology could countenance any hope for the ‘ungodly’ intruders. Further, it remains unclear what sorts of mercy or intervention could be envisioned and, thus, what Jude’s exhortations might really mean. This article surveys Jude’s eschatological horizon and the negative characterizations of the intruders and finds, ultimately, that the soteriology envisioned here allows a hope of mercy for the intruders. Further, it revisits Jude’s references to sin and judgment in scripture and illustrates how these narratives could also suggest paradigms of faithfulness and mercy to Jude’s audience.